Application of Wet Cupping Therapy in Reducing Blood Pressure among Patients with Hypertension - Ady Irawan AM; Aureo Frutalegio da Costa Frutalegio da Costa; Anggie Pradana Putri (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Cardiovascular disease includes hypertension as a risk factor. Cupping therapy is one of the complementary therapies that can be used to treat hypertension. In hypertensive patients, cupping therapy (Bekam) is a simple and cost-effective technique for lowering blood pressure.This study aims to identify the effectiveness of wet cupping for reducing blood pressure among patients with hypertension. This study employs a pre- and post-test design for a clinical observation. The participants in this study were all hypertensive patients from the Sukoharjo district in the province of Central Java, Indonesia. The study sample consisted of 27 intervention group participants and 29 control group participants. The bivariate statistics in this study were analyzed with Wilcoxon. The participants received wet cupping therapy at locations of the heart, namely points 4, 5, 6, 7, 8, for two weeks with a three-day interval between interventions, each lasting 30 minutes. There is a significant difference between pre- and post-test systolic and diastolic mean arterial pressure (MAP). In the first intervention, the mean systolic blood pressure was 18.3 mmHg (p = 0.000), and the mean diastolic blood pressure was 6.11 mmHg (p value of 0.003). After treatment, the mean diastolic pressure was 16.11 mmHg (p = 0.000) and the diastolic mean was 6.3 mmHg (p value of 0.000). Before intervention, the mean arterial pressure was 10.23 mmHg (p value = 0.000) and after intervention, it was 9.56 (p value of 0.000). This studies revealed that wet cupping therapy (Bekam Basah) is beneficial in lowering blood pressure in hypertensive patients.